STATE OF CHARGE ESTIMATION FOR AN ELECTRIC VEHICLE BATTERY - Morris Gibbson, Tamin (Universiti Malaysia Sarawak (UNIMAS), 2023)
The usage of electric vehicles has been increasing over the past decade globally. This is driven by the effort to reduce dependency of internal combustion engine (ICE) vehicles due to the global warming alerts by the environmental experts. As people began to explore the options of using electric vehicle (EV), the concern of battery or rather ‘battery anxiety’ has become a popular issue especially for new users transitioning from ICE vehicles to EV. State of charge (SOC) is the level of charge of a battery relative to the rated capacity and measured in percentage unit. It is the equivalent to the fuel level gauge for ICE vehicles. SOC cannot be measured directly because of the complexity of materials for different types of battery, thus it can only be estimated from measurement variables. Therefore, in this project which is State of Charge Estimation for Electric Vehicle Battery designed to estimate the SOC of a battery. The estimation of the SOC is crucial in the aspects of driving range estimation, battery health protection and to provide better charging routines. This project aims to simulate the battery SOC estimation with the Matrix Laboratory (MATLAB) Simulink and to compare the estimation methods and analyse the results from the simulation. Different methods will have different analysis on the SOC estimation due to external factors such as the battery model, the accuracy level, battery voltage, current, temperature and cell capacity.